2021
DOI: 10.1139/apnm-2020-0370
|View full text |Cite
|
Sign up to set email alerts
|

Whey protein supplementation and its potentially adverse effects on health: a systematic review

Abstract: Whey protein is composed of soluble whey proteins and its benefits are well described in the literature. However, there are not many studies investigating the potential adverse effect of a diet with indiscriminate use of this supplement. The aim of this study was to perform a systematic review of papers that addressed this theme. A search was conducted in Medline, Lilacs, Toxnet, Web of science, and Scopus electronic databases. In the end, 11 documents composed this review. The majority of the papers associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 60 publications
0
20
0
1
Order By: Relevance
“…Recent data [ 246 ] have shown that whey protein supplementation reduces fasting levels of anandamide and 2-AG without promoting weight loss in pre-menopausal women with obesity on a weight-loss diet. Interestingly, whey protein has also been suggested to modify the microbiota, although not necessarily with beneficial effects [ 247 ]. Indeed, the type of source of proteins and amino acids may also be crucial because two recent studies in obese mice have shown that: i) dietary essential amino acids affect gut microbiota composition and NAA levels in the adipose tissue and plasma of obese mice, thereby enhancing energy expenditure [ 248 ]; and ii) casein proteins instead exacerbate hepatic insulin resistance due to the increased gut microbial branched-chain fatty acids [ 249 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…Recent data [ 246 ] have shown that whey protein supplementation reduces fasting levels of anandamide and 2-AG without promoting weight loss in pre-menopausal women with obesity on a weight-loss diet. Interestingly, whey protein has also been suggested to modify the microbiota, although not necessarily with beneficial effects [ 247 ]. Indeed, the type of source of proteins and amino acids may also be crucial because two recent studies in obese mice have shown that: i) dietary essential amino acids affect gut microbiota composition and NAA levels in the adipose tissue and plasma of obese mice, thereby enhancing energy expenditure [ 248 ]; and ii) casein proteins instead exacerbate hepatic insulin resistance due to the increased gut microbial branched-chain fatty acids [ 249 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…Because of its high bioavailability and solubility, as well as a greater proportion of important amino acids, such as leucine, whey protein extract has been recommended as the best suitable form of protein for strength and endurance athletes, insulin secretion stimulation, and muscle protein oxidation prevention [14] [15] [16]. Amateur athletes, in particular, frequently consume whey protein on their own prescription, which they usually purchase directly from dealers or via websites, neglecting the potential hazards related to chronic and high intake of a specific nutrient, such as proteins [17]. A healthy adult population requires 0.8 g of protein per kilogram of body weight per day, according to a worldwide consensus.…”
Section: Introductionmentioning
confidence: 99%
“…I read with great interest the systematic review recently published by Vasconcelos et al (2021), which investigated the potential adverse effects of whey protein supplementation on health, including both human trials and animal models experiments (Vasconcelos et al 2021). Several review studies have shown beneficial effects of whey protein supplementation on human health, providing protection against a wide range of metabolic diseases such as dyslipidemia, hypertension, obesity, and type 2 diabetes (Badely et al 2019;Pal and Radavelli-Bagatini 2013;Patel 2015;Wirunsawanya et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, Vasconcelos et al (2021) presented that whey protein supplementation "may cause some adverse effects especially on kidney and liver function" (Vasconcelos et al 2021). This is the first systematic review that provides a warning on the potential adverse effects of whey protein supplementation but, unfortunately, some results have been misreported and the conclusions drawn by the authors are, in my view, unsubstantiated.…”
Section: Introductionmentioning
confidence: 99%